Combining ultra-high resolution ion mobility spectrometry with cryogenic IR spectroscopy for the study of biomolecular ions. (17th April 2019) - Warnke, Stephan; Ben Faleh, Ahmed; Pellegrinelli, Robert P.; Yalovenko, Natalia; Rizzo, Thomas R.
Abstract : We explore the capability of SLIM-based IMS for isomer selectivity in combination with cryogenic, messenger-tagging IR spectroscopy. Abstract : Double-resonance spectroscopic schemes in combination with cryogenic ion traps are the go-to techniques when isomer-specific high-resolution spectra are required for analysis of molecular ions. Their limitation lies in the requirement for well-resolved, isomer-specific absorption bands as well as in the potentially time-consuming steps to identify each isomer. We present an alternative approach where isomeric species are readily separated using ion mobility spectrometry (IMS) and selected prior to cryogenic spectroscopic analysis. To date, most IMS approaches suffer from relatively low resolution, however, recent technological developments in the field of travelling-wave ion mobility using structures for lossless ion manipulation (SLIM) permit the use of extremely long drift paths, which greatly enhances the resolution. We demonstrate the power of combining this type of ultra-high resolution IMS with cryogenic vibrational spectroscopy by comparing mobility-resolved IR spectra of a disaccharide to those acquired using IR–IR double resonance. This new approach is especially promising for the investigation of larger molecules where spectral congestion interferes with double resonance techniques.